A novel event-free survival endpoint in locally advanced pancreatic cancer. (November 2021) - Hammel, Pascal; Carrier, Ewa; Carney, Mairead; Eisner, Mark; Fleming, Thomas
The treatment paradigm for locally advanced pancreatic cancer (LAPC) is evolving rapidly. The development of neoadjuvant therapies composed of combination therapies and the evaluation of their impact on conversion to borderline resectable (BR) status, resection, and ultimately overall survival (OS) are presently being pursued. These efforts justify re-visiting study endpoints in order to better predict therapeutic effects on OS, by capturing not only the achievement of R0 resection at the end of induction therapy but also the long-term reductions in the rate of local and distal recurrence. The proposed herein event-free survival (EFS) endpoint, with its novel definition specific to LAPC, is formulated to achieve these objectives. It is an analog to disease-free survival (DFS) endpoint in the adjuvant setting applied to the neoadjuvant setting and may be a valuable surrogate endpoint for this patient population.